Trabeculectomy Augmented with Limited Deep Sclerectomy and Cyclodialysis with Use of Scleral Tissue as a Spacer - Tanuj Dada; Jyoti Shakrawal; Priyanka Ramesh; Anin Sethi (Journal of Ophthalmic & Vision Research)
Abstract Trabeculectomy remains the most commonly performed surgery for medically uncontrolled glaucoma. Its success in primary open angle glaucoma is approximately 82% in the initial year after surgery and 64% at the end of five years. Lower success rates have been found in secondary glaucomas like neovascular glucoma, uvietic glaucoma, post-traumatic glaucoma, and for repeat surgeries. To illustrate improvement of the efficacy of trabeculectomy, enhancement with cyclodialysis has been introduced. This involves the creation of a cyclodialysis cleft in a controlled manner to allow additional suprachoroidal drainage of the aqueous. Cyclodialysis is the result of the separation of the longitudinal ciliary muscle fibers from the scleral spur, which creates an additional pathway for aqueous humor drainage. However, such a cleft often closes on its own due to associated inflammation caused by the filtration surgery. Deep sclerectomy is a non-penetrating surgery that involves dissection of a scleral patch and excision of a block of scleral tissue, retaining a thin membrane for aqueous drainage. In this study, we introduce a novel surgical technique of combining trabeculectomy with a limited deep sclerectomy and a cyclodialysis in two pseudophakic patients who developed secondary glaucoma after vitreo-retinal surgery with silicone oil insertion. In this technique the excised scleral tissue obtained after deep sclerectomy was utilized as a spacer to maintain the patency of the cyclodialysis cleft.